Metastatic Insulinoma in a Patient with Type 2 Diabetes Mellitus: Case Report and Review of the Literature - Noormuhammad Oosman Abbasakoor; Marie Louise Healy; Donal O'Shea; Donal Maguire; Cian Muldoon; Kieran Sheahan; Dermot O'Toole (International Journal of Endocrinology)
Pancreatic neuroendocrine tumors (NETs) are extremely rare, and although insulinomas are the commonest, less than 10% of insulinomas are malignant. Most patients with insulinomas present with neuroglycopenic symptoms and weight gain attributable to insulin excess. Here, we report a case where a 67-year-old lady with a background history of type 2 diabetes mellitus and breakthrough hyperinsulinism who presented with coma. The biochemical profile revealed features typical of insulinoma, and CT and endosonography confirmed a pancreatic tumor with large volume right-sided liver metastases (biopsy confirming a neuroendocrine tumor). The patient underwent successful one-step RO surgical resection, distal pancreatectomy, splenectomy, and right hepatectomy, and 9 months postoperatively, she remains free of recurrent disease. She remains a diabetic.